3D printing formulation of probiotic extracellular vesicles for gastrointestinal cancer - Jaidev, Prapti (Nanyang Technological University, 2024)
Despite the well-documented immunomodulatory effects of probiotic-derived extracellular vesicles (EVs) in treating gastrointestinal (GI) related diseases, a significant challenge limiting their therapeutic efficacy arises from their vulnerability to gastric acid degradation when administered orally. Hence, this project aims to address this issue by developing a formulation using 3D bioprinting techniques to encapsulate probiotic EVs, ensuring their preservation in low pH environments and facilitating targeted release in intestinal conditions.